Role of Psychological Factors as a Determinant of the Hypercapnic Ventilatory Response and Dyspnea Sensation - Kawakami, Yoshikazu; Kobayashi, Shyuichi; Yamamoto, Makoto; Nishimura, Masaharu; Akiyama, Yasushi; Miyamoto, Kenji (Nihon Kyōbu Shikkan Gakkai zasshi, 1992)
We examined, in 38 healthy adult subjects (male 15, female 23), the relationship between psychological background as assessed by manifest anxiety scale test and Yatabe-Guillford test, and the hypercapnic ventilatory response (HCVR), which was tested twice with and without inspiratory resistive loading (17cmH2O/L/sec). In addition, we attempted to evaluate the possible role of psychological factors in dyspnea sensation felt during HCVR, which was simultaneously assessed by visual analogue scaling (VAS). The slope value of HCVR was positively correlated with the social extraversion score in the male group (r=0.55, p<0.05) only when the test was conducted without resistive loading. In the female group, it was positively correlated with emotional instability in both conditions (r=0.46, p<0.05 without resistive loading and r=0.47, p<0.05 with resistive loading). With respect to dyspnea sensation, manifest anxiety score alone had a positive correlation with VAS score evaluated in relation to ventilation only in the male group (r=0.61, p<0.05). From these findings, we conclude that psychological factors may play a role as a determinant of HCVR, regardless of the presence of inspiratory resistive loading, as well as a determinant of the sensation of dyspnea during HCVR.